PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI PADA PENGELOLAAN TAHU TEMPE KELAPA GADING TEMBILAHAN - Ranti Melasari; Ira Gustina; Yusriwarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
Management of Tofu Tempe Kelapa Gading Tembilahan is a form of business that can provide many benefits and benefits for the community. There are several obstacles faced by SMEs. One of these obstacles is the lack of knowledge of MSME actors in financial aspects, such as determining the Cost of Production (HPP) as the basis for determining the selling price of products. Based on the results of initial observations, the servant received information about the lack of assistance from business actors in determining the cost of production and selling prices of products. Therefore, this community service activity was carried out to help solve these problems. The main activity carried out in this community service activity is assistance in determining the cost of production and the selling price of the product. The purpose of this activity is to increase the understanding of MSME actors in determining the Cost of Production (HPP). The method used in this activity is the case study method and direct assistance to business actors in calculating the cost of production of their business and the selling price of their products. Based on the results of the evaluation, the understanding and skills of MSME actors increased after the implementation of this assistance. This can be seen from the way MSME actors determine the selling price by calculating the production costs first.